2017
DOI: 10.1136/bjophthalmol-2016-309814
|View full text |Cite
|
Sign up to set email alerts
|

Putative protective role of lutein and zeaxanthin in diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is one of the most important microvascular complications of diabetes and remains the leading cause of blindness in the working-age individuals. The exact aetiopathogenesis of DR remains elusive despite major advances in basic science and clinical research. Oxidative damage as one of the underlying causes for DR is increasingly being recognised. In humans, three hydroxycarotenoids, lutein (L), zeaxanthin (Z) and -zeaxanthin (MZ), accumulate at the central retina (to the exclusion of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 82 publications
0
57
0
Order By: Relevance
“…It is important to stress that the Mediterranean diet also allows the intake of fat-soluble antioxidants, among which carotenoids, such as lutein, zeaxanthin, astaxanthin, -carotene, -carotene, lycopene, etc., are certainly one of the most well represented groups in foods of vegetal origin [4]. Several studies indicated that these compounds, due to their capacity to scavenge reactive oxygen species (ROS) [5], may exert beneficial effects in different pathological states characterized by increased ROS production, such as neurodegenerations [6], myocardial ischemia [7], diabetic retinopathy [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to stress that the Mediterranean diet also allows the intake of fat-soluble antioxidants, among which carotenoids, such as lutein, zeaxanthin, astaxanthin, -carotene, -carotene, lycopene, etc., are certainly one of the most well represented groups in foods of vegetal origin [4]. Several studies indicated that these compounds, due to their capacity to scavenge reactive oxygen species (ROS) [5], may exert beneficial effects in different pathological states characterized by increased ROS production, such as neurodegenerations [6], myocardial ischemia [7], diabetic retinopathy [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is also useful in process of beverage fermentation (Anthony et al, 2001). The valine content of the leaves (3.170 g/100 g) and fruits (2.581 g/100 g) of D. dewevrei was found to be higher to D. guineense (Ayessou et al, 2014;Kumari, Catherina, Katherine, Chew, & Kah-Guan, 2017). Nonessential amino acids are said to be dispensable because the body can synthesize them readily.…”
Section: Discussionmentioning
confidence: 99%
“…Astaxanthin has proven to be efficient against OS as an antioxidant, in addition to having anti-inflammatory and antiapoptotic properties, underlining its importance in neurodegeneration in DR [73]. In preclinical studies, this xanthophyll has shown to decrease OS damage-induced biomarkers and to increase glutamine synthetase concentrations in Müller cells, reducing apoptosis in retinal ganglion cells as seen in Figure 2 [74,75]. Astaxanthin can also regulate glycemic states and reduce insulin resistance and exert an antiinflammatory effect by decreasing the expression of NF-κβ and TNF-α [76] and by inhibiting the expression of proinflammatory molecules such as ICAM-1 and monocyte chemoattractant protein-1 (MCP-1) and angiogenesis via VEGF [66].…”
Section: Supplement Therapies and Diabetic Retinopathymentioning
confidence: 99%